Pengaruh Liquidity, Leverage, Profitability, Sales Growth, dan Firm Size Terhadap Cash Holding - Shafa Almaidah YefriNanda; M Hendri Yan Nyale (Universitas Sains dan Teknologi Komputer, 2026)
This research analyzed the influence of liquidity, leverage, profitability, sales growth, and firm size on cash holdings. The research is quantitative, using secondary data from annual financial reports of primary consumer industries listed on the Indonesia Stock Exchange from 2022 to 2024. Liquidity is measured by the Current Ratio, which is calculated as current assets divided by current liabilities. Leverage, proxied by the Debt-to-Equity Ratio, is measured by total liabilities divided by total equity. Profitability, proxied by Net Profit Margin, is calculated using the formula operating profit divided by sales. Sales Growth is measured as the current total sales minus the previous total sales, divided by the previous total sales, expressed as a %. Firm Size is proxied by the natural logarithm of total assets. Meanwhile, Cash Holding is measured by cash and cash equivalents divided by total assets. This research was conducted using a sample of 174 data points from 58 companies; outliers were removed, resulting in 159 data points from 53 companies. The sampling was done using purposive sampling. The research results indicate that liquidity has a positive effect on cash holding. Leverage has a negative effect on cash holding. Profitability has a positive effect on cash holding. Sales growth has a positive effect on cash holdings. Firm size has a positive effect on cash holding.